The good wife. The fourth season [videorecording (DVD)] - Margulies, Julianna, 1966-; Baranski, Christine; Charles, Josh, 1971-; Noth, Chris, 1954-; Cumming, Alan, 1965- (Paramount Home Entertainment, 2013)
A gripping blend of courtroom drama, politics and steamy personal relationships that stars Emmy and Golden Globe Award winner Julianna Margulies as Alicia Florrick, a wife and mother who reclaims control of her personal and professional lives after her husband, Peter, is embroiled in a sex and political corruption scandal. As Alicia adapts to changes at home and at work as a defense attorney, she continues to redefine and rediscover the woman she wishes to be.